The Generic Reasons for Strikes: An Interpretative Analysis of the Israëli Case - Blum, Albert; Harel, Gedaliahu (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
The purpose of this paper is to reveal those universal socio-economic conditions which generally foster strikes, and the most general labor relations-related reasons for conflicts which eventually result in strikes.